Pengaruh Perubahan Perilaku Pengunjung pada Pusat Perbelanjaan Pasca Pandemi, Studi Kasus: Mall Blok M dan Plaza Semanggi - Ramadhan, Naufal Fadillah; Nugroho, Agung Cahyo (Universitas Bandar Lampung (UBL), 2025)
Abstract: This study aims to investigate the factors that lead to the lack of visitor visits in two old malls in Jakarta, namely Mal Plaza Semanggi and Mal Blok M. The research method used is quantitative analysis by analyzing and identifying people who have visited the two malls. The study population included 50 respondents who filled out the online form from various regions. The inclusion criteria were those who had visited Mal Plaza Semanggi or Mal Blok M, and had visited other large malls in Jakarta besides these two malls. The results showed positive indications that Plaza Semanggi Mall and Blok M Mall experienced a decline in visitation after the pandemic, while other large malls managed to recover from the impact of the pandemic. Respondents gave a negative impression of Mal Plaza Semanggi and Mal Blok M